Surmounting the endothelial barrier for delivery of drugs and imaging tracers. (December 2020) - Schnitzler, Johan G.; Dzobo, Kim E.; Nurmohamed, Nick S.; Stroes, Erik S.G.; Kroon, Jeffrey
Abstract: The endothelium is crucial for maintaining vascular homeostasis and functions as a barrier between blood components and tissue. In atherosclerosis, this barrier function is impaired, which is characterized by secretion of chemoattractants and cytokines, upregulation of adhesion molecules and increased vascular permeability. This facilitates enhanced leukocyte migration through the vessel wall. Fortunately, we can utilize these features to our advantage by using nanomedicine to deliver drugs and imaging tracers into the interstitial space. This provides us with targeted, local delivery of therapeutic agents, which enhances the specificity and efficacy of these agents and thus, could be used to inhibit disease progression. Additionally, delivery of imaging tracers in the interstitial space will give us insight into the vulnerability of atherosclerotic plaques by targeting resident macrophages and activated endothelial cells, providing pivotal information that is currently lacking in the clinic. In this review, we discuss how the endothelial barrier is affected during atherosclerosis and how to surmount this barrier for successful delivery of nanomedicine carrying drugs and imaging tracers to both the endothelium and macrophages. Graphical abstract: Image 1 Highlights: The endothelium serves as a refined barrier, crucial in guarding vascular homeostasis. Impaired endothelial barrier function offers opportunities for targeted delivery of therapeutic agents/imaging tracers. Nanosized technology provides the ability to distinguish between stable and rupture-prone atherosclerotic plaques. The 'Trojan Horse Strategy' fools the endothelium and immune system in order to specifically deliver drugs at target sites.